ANALISIS NILAI OVERALL EQUIPMENT EFFECTIVENESS PADA MESIN PACKER FOCKE FX 2 DI PT ABC - Reditya Chiesa Ramadhan; Unung Lesmanah; Mochammad Basjir; Nur Robbi; Rangga Ega Santoso (Universitas Islam Malang, 2025)
This study carried out to overcome the performance and efficiency problems of the Packer Focke FX 2 machine at PT. ABC. The study uses descriptive quantitatie approach to analyze Overall Equipment Efetiveness (OEE) value. The resultof OEE value is analyzed by Six Big Losses method to find the losses factors and used the failure mode Effect Analysis (FMEA) method with fishbone diagram to find its root causes and provide suggestion for improvement. The result of the study is OEE value from the period of June 2024 to Ugust 2024, which was 43,4 %. This result is lower than the world standart OEE of 85 %. These result are caused by high value of idling and minor stoppage losses at 15,84% and breakdown losses at 13,46%. The root of problems was found using FMEA method with RPN value of 288, which is failure in blank feeding process with type of failure mode is blank material jamming in blank track area because of spray glue jet was not function optimally. So that, the recommendation of improvements that are given are related to preventive method, spare part management, and employee competency